2004
DOI: 10.1007/978-3-540-30537-8_27
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Network and Web-Based Decision Support System for Forex Forecasting and Trading

Abstract: Abstract. This study presents a neural network & web-based decision support system (DSS) for foreign exchange (forex) forecasting and trading decision, which is adaptable to the needs of financial organizations and individual investors. In this study, we integrate the back-propagation neural network (BPNN)-based forex rolling forecasting system to accurately predict the change in direction of daily exchange rates, and the Web-based forex trading decision support system to obtain forecasting data and provide so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Recent achievements have shown that it is also of great use to combine different neural networks into recommender systems. There are many works which employed neural networks to improve the recommendation in the domain of recommender systems [3][4][5][6][7] and in the context of web-based decisions [8][9][10][11][12]. The success of these recommendation approaches based on neural networks demonstrates its capability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent achievements have shown that it is also of great use to combine different neural networks into recommender systems. There are many works which employed neural networks to improve the recommendation in the domain of recommender systems [3][4][5][6][7] and in the context of web-based decisions [8][9][10][11][12]. The success of these recommendation approaches based on neural networks demonstrates its capability.…”
Section: Introductionmentioning
confidence: 99%
“…Ada beberapa penelitian tentang prediksi forex menggunakan model backpropagation yang telah dilakukan yaitu dari Joarder Kamruzzaman, dkk [10] [11] menyajikan dukungan jaringan & web berbasis pengambilan saraf sistem (DSS) untuk valuta asing (valas) peramalan dan keputusan trading, yang disesuaikan dengan kebutuhan lembaga keuangan dan investor individu. Dalam karya penelitian K.K.…”
Section: Pendahuluanunclassified
“…Generally, tabular patterns can have more dimensions. Graphical representation of OHLC data (Lai, 2005) in Fig.2 is a good example of the expression of multidimensional data projection to two-dimensional space. Fig.2 shows a visual representation of 4-dimensional vector in time, which corresponds to 5 -dimensions.…”
Section: Fig 1 Tasks In the Pattern Recognition Systemsmentioning
confidence: 99%